Emotions, senses, spaces: Ethnographic engagements and intersections - Hemer, Susan R.; Dundon, Alison (The University of Adelaide Press, 2016)
This volume draws together three core concerns for the social sciences: the senses and embodiment, emotions, and space and place. In so doing, these collected essays consider the ways in which these core concerns are mutually constitutive. This includes how spaces evoke, constrain or are composed by the senses and emotions; the ways in which emotions are generated or transformed in certain spaces and through sensual engagement; and the processes by which embodied senses create spaces and emotions. The chapters engage with intersections between space, sense and emotion through a range of experiences and activities including dance, bullfights, healing ceremonies, celebrations and music. The authors herein critically examine diverse contexts, in and through which relations between sensate bodies, spaces and places, and emotions are constituted. The chapters draw on long-term ethnographic fieldwork from which the authors critically engage with their material on a fundamental level and contribute to contemporary debates about the nature and experience of emotions, the sensing body, and spaces and places.
Keywords: anthropologie; corps; discipline; ethnographie; genre; ressource en ligne; sciences humaines; thématiques; émotions

Ethnographier la violence dans la prostitution : effets du contexte, effets du terrain et force des émotions - Mayer, Sibylla (Parcours antrhopologiques, 2016)
Dans cet article, je prends pour objet une enquête passée, menée sur la prostitution de rue. Partant du vécu d’une émotion forte en aval de la recherche, après la sortie du terrain et après la discussion des résultats, je m’interroge sur la place des émotions dans l’enquête, en particulier en lien avec l’ethnographie de la violence dans la prostitution. En revenant sur le meurtre d’une personne connue sur le terrain et sur ce que cet événement a suscité en termes de retour sur ma démarche, je montre notamment que les émotions agissent en modifiant notre vécu, y compris en aval du terrain, nous permettant de revenir sur notre positionnement face à l’objet de recherche.
https://journals.openedition.org/pa/495
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; discipline; ethnographie; europe; luxembourg; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; travail du sexe; violences; émotions